MONITORING OF SURFACE RESOURCES OF WATER SUPPLY IN THE CONDITIONS OF IMPLEMENTATION OF WATER FRAMEWORK DIREKTIVES OF EU: Array - Bezsonnyi, V. (Municipal economy of cities (Technical science), 2019)
Monitoring of ecological safety of surface sources of drinking water supply is an integral part of the state monitoring system. The monitoring system is not yet fully compliant with international requirements. The current regulatory framework for assessing the quality of surface water is not sufficiently integrated with the regulatory framework of advanced European countries. In Ukraine, in recent years, in accordance with the Government's decisions, harmonization of national environmental regulatory documents with the relevant normative documents of highly developed countries of Europe and the world is carried out. The main shortcomings of the existing monitoring system are: the lack of interaction and information exchange between services that control the use and protection of water resources; the impossibility of operative registration of accidental pollution of the watercourse due to the lack of continuous monitoring systems for water quality characteristics; lack of transmission systems and operative data processing on the basis of modern communication facilities and computer equipment; insufficient account of transboundary pollution transfer between regions, united territories of river basins; the lack of effective accounting for the pollution of the surface runoff. For the rational use of available resources, four levels of analytical monitoring of water monitoring are proposed. First level: stationary emergency control posts. The second level: stationary laboratories. Third level: central analytical control labs. Fourth level: remote sensing information reception and processing centers. It is suggested, when determining the category of the observation point, to take into account the volume of water consumed and discharged by the consumers of the water, for which it is necessary to determine the number of water users located on the investigated watercourse. Recommendations for improving the monitoring network of the environmental monitoring system in the light of the EU Water Framework Directive are proposed by reviewing approaches to determining the number of observation points in control units. The Water Framework Directive provides that the monitoring program should make it possible to compare the environmental status with the reference conditions, and not only reflect the degree of exposure of individual substances, therefore it is considered appropriate in the future, when implementing the provisions of the Water Framework Directive in the practice of monitoring water, in constructing a network of observation points to restrict only one section below the source of pollution, since for each reservoir and watercourse there will be values of indicators of the content of chemicals and other characteristics for water reference (background) condition.